The Prime Minister and Cabinet - Buckley, Stephen (Politics study guides., 2006)
This introduction to the workings of the Prime Minister and Cabinet is written in light of major recent events and issues such as the war with Iraq, the Hutton Inquiry, the Butler Report, the Blair-Brown relationship, and continuing problems relating to Europe. These are presented in the context of the origins of the office of Prime Minister and the development of Cabinet government. Key issues covered include: The nature of Prime Ministerial power The continuing debate surrounding the nature of the Cabinet and decision-making The development and workings of the core executive Changes since the 2005 general election The continued impact of UK membership of the EU This insightful volume gives readers an overview of the Blair premiership and the workings of a Labour Cabinet at a time when both are facing increased criticism and pressure. Key Features: Takes account of the impact of the 2005 general election Considers issues central to the Blair government: Iraq, personal honesty, leadership manoeuvring, and the probable nature of the government Blair will leave behind him Offers close analysis of Blair's 'inner court' of advisers Presents an up-to-date overview of Blair's political style